Impacts of Oil Price Shock on Sector Returns with Regime-Switching Approach: New Evidence from Indonesian Stock Market - Dharmawan, Mohammad A.; Priyarsono, Dominicus S.; Sartono, Bagus (International Journal of Energy Economics and Policy, 2017)
This study investigates the impacts of an oil price shock on sector returns in the Indonesian stock market. Oil prices and the stock market are both important elements of the Indonesian economy. The research attempts to characterize the impacts and causality relationship between oil price shocks and sector returns, with time segmentation based on structural breaks in oil price data from 1996 to 2016. We applied structural-break analysis to oil prices using the Bai-Perron procedure and identified three break points, thereby dividing the data set into four different regimes. We analyzed the impacts of oil price shocks and sector returns using an unrestricted Vector Autoregression (VAR) model. The findings indicated that impacts of the oil price shocks on sector returns vary, depending on the regime in which the shocks occurred. In general, during low and stable oil price regimes, the impacts of oil price shocks on sector returns were not significant, whereas for high oil price and high volatility regimes, oil price shocks affected some sectors significantly. Keywords: oil price shock, stock returns, vector autoregression JEL Classifications: C22, E44, G11